Effect of unilateral and bilateral plyometric training on jumping, sprinting, and change of direction abilities: a meta-analysis - Zhang, Z.; Qu, W.; Peng, W.; Sun, J.; Yue, J.; Guan, L.; Lu, M.; Li, D. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Plyometric training is a commonly employed method to enhance explosive strength in athletes. However, to date, no study has provided a comprehensive and systematic evaluation of the effects of unilateral (UNI) versus bilateral (BI) plyometric training.